Inscreasing Learning outcome of PGSD Students Using Problem-Based Learning Model in IPS Basic Concept Courses Era Pandemic Covid-19 - Kristi Wardani; Gusti Izhar (Edukasi, 2023)
This study aims to improve student learning outcomes using the Problem Based Learning model. This study uses a collaborative classroom action research model of Kemmis and Mc Taggart. The research subjects were the second-semester students of Class A Universitas Sarjanawiyata Tamansiswa consisting of 44 people. Data collection uses interview, observation, test, and documentation techniques as supporting data. Quantitative data were analyzed using descriptive statistics by looking for the mean. Qualitative data were analyzed using qualitative descriptive.The learning process to improve student learning outcomes uses the Problem Based Learning model. The results showed that the use of this model in learning can improve student learning processes, especially learning outcomes. This is evidenced by the increase in learning outcomes which in the first cycle reached the classical percentage of 56.8% to 88.6% in the second cycle.